2006
DOI: 10.1103/physrevb.73.045336
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of site-specific valence electronic structure at theSiO2Siinterface

Abstract: Atom specific valence electronic structures at interface are elucidated successfully using soft x-ray absorption and emission spectroscopy. In order to demonstrate the versatility of this method, we investigated SiO 2 /Si interface as a prototype and directly observed valence electronic states projected at the particular atoms of the SiO 2 /Si interface; local electronic structure strongly depends on the chemical states of each atom. In addition we compared the experimental results with first-principle calcula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
4
21
0
1
Order By: Relevance
“…To visualize the real-space band structure across the interface, we evaluate the real-space density of states ρðz; EÞ projected onto the normal direction z of the interface [54][55][56][57][58][59][60][61]. This projection is calculated for majority and minority spins σ ¼ AE as…”
Section: Gdn=gan (011) Interfacementioning
confidence: 99%
“…To visualize the real-space band structure across the interface, we evaluate the real-space density of states ρðz; EÞ projected onto the normal direction z of the interface [54][55][56][57][58][59][60][61]. This projection is calculated for majority and minority spins σ ¼ AE as…”
Section: Gdn=gan (011) Interfacementioning
confidence: 99%
“…A narrower band gap for suboxides in a SiO 2 /n-type Si(111) interface region is calculated by Yamashita et al 24 They have shown that the main oxides in a thin interface region between a Si substrate and a SiO 2 film are Si 2 O and Si 2 O 3 and that the band gap increases as the oxidation state increases (E g ðSi 2 OÞ < E g ðSi 2 O 3 Þ < E g ðSiO 2 Þ). A different band gap alignment of the ITO/Si interface than in the case of SiO 2 as the main silicon oxide and the presence of metallic In and Sn at the interface may play a significant role in the carrier transport mechanism in the ITO/Si junction.…”
mentioning
confidence: 98%
“…2(d)). According to the previous study, these edge structures were attributed to valence band maximums (VBMs) of the suboxide species [7]. Thus, the VBMs, conduction band minimums (CBMs), and band-gaps (E g s) of the suboxide species are obtained, which is summarized in Table I.…”
Section: Resultsmentioning
confidence: 89%
“…Recently we successfully observed conduction and valence electronic structures at solid-solid interfaces directly using soft x-ray absorption (SXA) and emission (SXE) spectroscopy [7][8][9]. This method is based on site-specific photo absorption and emission, which gives us the local valence electronic states at the interface [10,11].…”
Section: Introductionmentioning
confidence: 99%